Relationship between effects of climate and the late blight (Phytophthora infestans (Mont.) de Bary) in the potato (Solanum tuberosum L.) crop - Wilches Ortiz, Wilmar Alexander (2022)
Potato (Solanum tuberosum) is the fourth most important crop worldwide. The crop is affected by the climate variability, mainly in relation to diseases severity and pathogens survival, which is the case of late blight caused by Phytophthora infestans. The objective of this study was to evaluate the effect of the climatic elements on late blight severity. The study was carried out in the municipality of Mosquera, Cundinamarca, Colombia, from December 2015 to May 2016. The potato varieties Diacol Capiro (DC), ICA-Unica (IU) and Pastusa Suprema (PS) were included in this study. Data of late blight severity together with data of precipitation (Pr), relative humidity (RH), temperature (T), wind speed (VV), solar brightness (BS) were recorded, and with these data the agroclimatic indices water index (IH), temperature degree day (GD) and evapotranspiration reference (ETo) were calculated. There was a significant positive correlation (p < 0.05) of late blight severity in the three varieties with IH (0–158 ± 58), precipitation (0–63 mm ± 23 mm) and minimum temperature (2-10 °C ± 2 °C), and significant negative correlation (p < 0.05) of P. infestans severity with BS (2–7.7 h day-1 ± 1.7 h day-1). The GD (0–4 °Cd ± 1 °Cd) presented a significant positive correlation with DC and PS, and also positive correlation with the mean temperature (11–15.3 °C ± 1.41 °C) with DC. The ETo (0.4–3.3mm day-1 ± 0.87mm day-1) and maximum temperature (19.9–23 °C ± 0.75 °C) were significantly and negatively correlated with DC and PS, and also between VV (5 .27–7.95 km h-1 ± 0.79 km h-1) with DC. It was concluded that climatic variables influenced late blight severity and P. infestans survival.